Susceptibility of Aedes aegypti and Aedes albopictus to temephos in four study sites in Kuala Lumpur City Center and Selangor State, Malaysia - Chen, C.D.; Nazni, W.A.; Lee, H.L.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2005)
Larvae obtained from Taman Samudera (Gombak, Selangor), Kampung Banjar (Gombak, Selangor), Taman Lembah Maju (Cheras, Kuala Lumpur) and Kampung Baru (City centre, Kuala Lumpur) were bioassayed with diagnostic dosage (0.012 mg/L) and operational dosage (1 mg/L) of temephos. All strains of Aedes aegypti and Aedes albopictus showed percentage mortality in the range of 16.00 to 59.05 and 6.4 to 59.50 respectively, after 24 hours. LT50 values for the 6 strains of Ae. aegypti and Ae. albopictus were between 41.25 to 54.42 minutes and 52.67 to 141.76 minutes respectively, and the resistance ratio for both Aedes species were in the range of 0.68 to 1.82 when tested with operational dosage, 1 mg/L temephos. These results indicate that Aedes mosquitoes have developed some degree of resistance. However, complete mortality for all strains were achieved after 24 hours when tested against 1 mg/L temephos.